Study on the Dynamic Instability Mechanism of the Rock Formation in the Multifault Structure Zone of the Stope. (29th March 2022) - Guo, Hanxiao; Yu, Weijian; Liu, Yong; Zhang, Zongtang; Kang, Xiangtao
Abstract : Under the influence of tectonism in geological activities, most fault structures appear in groups. Multiple fault structures can induce a variety of mine dynamic disasters, which significantly affect the safety of mine production. To study the dynamic instability mechanism of the strata in the multifault structure zone of the stope when mining, a numerical model of multiple fracture structures was established. At the same time, the mechanism of the dynamic instability of the rock formation in the multifault structure zone of the stope has been studied through similar simulation experiments and on-site data analysis. The research results show that the stress-affected areas of the faults in the multiple-fault structure area overlap, and the stress evolution law of the fault will distinguish its independent dynamic evolution model. The multifault structure area has a multifault overall evolution law model. In this model, there is a synergy between the fault layers, and the maximum value of stress concentration is diagonally distributed. Under the influence of mining, the fault structure will be activated to change the stress field distribution form of the stope. The two faults in multiple structural areas have a joint mechanism, which plays a key role in controlling the dynamic instability process of the surrounding rock of the stope. The first activated faults in the multiple-fault structure area will undergo secondary activation under the influence of subsequent fault activities. The evolution law of cracks in the overburden of similar simulation experiments confirms that the early active F1 fault will be affected by the subsequent F2 fault activity. The mine pressure data measured on-site verifies the reliability of the numerical simulation experiment and the similar simulation experiment.